2017
DOI: 10.3345/kjp.2017.60.9.302
|View full text |Cite
|
Sign up to set email alerts
|

Serum neuron specific enolase is increased in pediatric acute encephalitis syndrome

Abstract: PurposeThis study aimed to investigate whether serum neuron-specific enolase (NSE) was expressed in acute encephalitis syndrome (AES) that causes neuronal damage in children.MethodsThis prospective observational study was conducted in the pediatric neurology ward of Soetomo Hospital. Cases of AES with ages ranging from 1 month to 12 years were included. Cases that were categorized as simple and complex febrile seizures constituted the non-AES group. Blood was collected for the measurement of NSE within 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“… 49 Inflammation may play an important role in neuronal injury, and previous study showed that serum NSE was remarkably increased in acute encephalitis syndrome. 50 Matrix metalloproteinase-9 is a gelatinase linked to BBB extracellular matrix degradation released by inflammatory cells. 51 Haque et al reported that inhibition of NSE activity decreased matrix metalloproteinase-9 expression and inflammatory reaction in spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Inflammation may play an important role in neuronal injury, and previous study showed that serum NSE was remarkably increased in acute encephalitis syndrome. 50 Matrix metalloproteinase-9 is a gelatinase linked to BBB extracellular matrix degradation released by inflammatory cells. 51 Haque et al reported that inhibition of NSE activity decreased matrix metalloproteinase-9 expression and inflammatory reaction in spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to know the biomarkers of nerve damage in infection to predict the disease's outcome and severity. 9 Neuroimaging is very important in establishing the diagnosis of ADEM. The demyelinating lesions of ADEM were most clearly seen using MRI, T2-weighted images, and fluid-attenuated inversion recovery (FLAIR).…”
Section: Case Reportmentioning
confidence: 99%
“…1 There have been many studies on the correlation of biological uid biomarkers with neurological disorders. 9 Lactate levels as a biomarker will increase in the rst few hours after the seizure. Formerly the seizure has terminated, the lactate production reduces and it will rapidly cleared.…”
Section: Introductionmentioning
confidence: 99%